CSR achievement, reporting, and assurance in the energy sector: Does economic development matter?. (February 2021) - Karaman, Abdullah S.; Orazalin, Nurlan; Uyar, Ali; Shahbaz, Muhammad
Abstract: Drawing on signaling theory and the greenwashing tendency, the objective of this study is to explore the connection among four facets of corporate social responsibility (CSR) practice: CSR performance, CSR reporting, following the Global Reporting Initiative (GRI) guidelines in preparing CSR reports, and verifying the reliability of CSR reports through an external assurance statement. The sample of the study includes 2244 firm-year observations of energy firms listed in the Thomson Reuters Eikon database for the period 2012–2018. Panel data analysis with fixed effects is used as the empirical methodology. The findings lend support to signaling theory and reject a greenwashing tendency in the energy sector with the validation of hypothesized relationships. More specifically, higher CSR performers show their CSR commitment by issuing CSR reports as well as by adopting GRI guidelines in their CSR reports and verifying the reliability of the contents of their reports through an external assurance statement. Moreover, GRI framework adopters are more likely to obtain external assurance of their reports. The examination of these relationships considering the economic development levels of countries highlights notable differences: all hypothesized connections are stronger for firms established in middle-income countries than for those in high-income countries except for one dimension. Highlights: The findings lend support the signaling theory and reject a greenwashing tendency in the energy sector. Firms with superior CSR performance are more likely to issue a CSR report and adopt the GRI framework. Firms with superior CSR performance are more likely to assure their CSR reports externally. Adopters of the GRI framework are more likely to assure their CSR reports externally. Overall, CSR commitment is stronger for firms in middle-income countries than those in high-income countries.